Effect of Plant Extracts on the Postharvest Performances of Vegetables (South Asian Journal of Agriculture, 2019)
Plant extracts are recognized as safe and low-cost materials for postharvest treatments to increase the shelf life of horticultural commodities. However, in Bangladesh plant extracts are rarely used and very little research outcomes have been reported in Bangladesh context. Hence the current study was conducted to evaluate the effectiveness of combined botanical extracts in maintaining postharvest physico-chemical properties and extending shelf life of some summer vegetable (Bitter gourd, Brinjal and Pointed gourd) of Bangladesh. Freshly harvested vegetables were left untreated (control- T1) or treated with combination of aloe vera and thankuni extracts (T2); onion, garlic and ginger extracts (T3); aloe vera, thankuni, onion, garlic and ginger extracts (T4). Then they were kept for two weeks in uncovered paper carton in ambient conditions to observe their postharvest performances in respect of microbial infection (%), total soluble solids (% Brix), pH (magnitude), ascorbic acid content (mg/100 g), weight loss (%), shelf life (days), firmness (score) and color (score). In comparison to the control (T1), the postharvest properties were well maintained in T2 treated bitter gourd, and T4 treated pointed gourd and brinjal as recorded accordingly for shelf life (7.33, 6.63 and 7.30 days), content of vitamin C (39.56, 48.83 and 1.4 mg/100g), microbial infection (14.64%, 0% and 3.53%), rate of pH reduction (22.59%, 10.59% and 15.45% ), loss of fresh weight (1.39, 1.82 and 1.65-fold lower than T1) and color and firmness scores (1.22 and 1.36; 1.19 and 1.23; 1.8 and 1.39-fold higher than T1). From the current study it could be concluded that, the combination of aloe vera and thankuni extract would be considered as a suitable treatment for maintaining postharvest properties in bitter gourd. For pointed gourd and brinjal, the combination of aloe vera, thankuni, onion, garlic and ginger extract would be a suitable extract in this regard.South Asian J. Agric., 7(1&2): 38-43